Pemberdayaan Masyarakat Dalam Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPKKS) - Nurul Inayah; Nur Anim Jauhariyah; Lely Ana Ferawati Ekaningsih; Muhammad Hasbullah Ridwan (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2019)
This service aims to train the people in Sukomukti Hamlet, Sukorejo Village, Bangorejo Subdistrict, Banyuwangi Regency in managing the financial business of the family in an effort to support the government's program to Increase Prosperous Family Income (UPPKS) in Banyuwangi Regency. The approach taken in this service is the method of participatory action research (PAR). The results of the management of the financial management system in the Sukomukti Hamlet community were maximally absorbed so that the community was able to manage finances well and was supported by adequate conditions in managing finances